SEARCHING FOR THE SOURCES OF 18TH AND 19TH CENTURY LATGALIAN RELIGIOUS SONGS - Kalvāne, Skaidrīte (Via Latgalica, 2016)
Latgalian „svātuos dzīsmis” (‘sacred songs’) were not only sung in the church in the 18th and 19th centuries. These songs became integral and necessary components of both home and spiritual life.Some publications of spiritual song and prayer books written by the Latvians of Latgale have been preserved until today: „Nabożeństwo” (1771, 1786, etc.) and „Dzismies Swatas” (1801, etc.). Of these are both first editions and reissues. These compilations represent the basic core of 19th century spiritual songs in conjunction with the book „Piļneigajā gruomotā lyugšonu” (“The Complete Book of Prayers”) published in the latter half of the century. Psalms which were written well before the birth of Christ are among the oldest religious songs. Psalms of penance and prayers for the dead were first published in Latgalian in the 1786 edition of „Nabożeństwo”.The diversity of genres of songs is surprising: songs using scriptural texts, hymns of the Fathers of the Church, sequences and antiphonies. The progress of the liturgical year was supported by additional processionary hymns, hour songs (godzinkas), descriptions of the lives of saints set to music, catechism songs and prayers which are written as prose but given a melody in order to be sung. Directly arrhythmic language and certain metrical text used for worship in prayers made it unclear exactly how many texts were in fact songs.It is not possible to determine the authors of all songs. Text recognition is also hampered by the lack of a printed Polish source – the work that the Jesuits translated to create the hymnals has not been found. Thus, for comparison of these texts it is necessary to find them in various books or consult the wider body of 19th century songs, wherein the content of songs is usually altered. The “sacred songs” examined and analyzed in this article were selected at random. The majority of songs so far sourced are from „Nabożeństwo”, but identification work continues at present.